Gestão da política de assistência social: uma análise da realidade de Miracema do Tocantins - TO (2017/2018) - Rodrigues, Regileny Camargo (Universidade Federal do Tocantins, 2021)
This paper entitled "Management of Social Assistance Policy: an analysis of the reality of Miracema do Tocantins - TO (2017/2018)" aimed to show the challenges experienced by the actors involved in the Social Assistance policy of the Municipality of São Paulo . Based on the decision-making processes and management tools executed for the execution of projects in SUAS and in the administrative part, as well as for the processes that involve the progress of the Assistance Policy issues . in a critical perspective, based on Marx's social theory. For an approximation of the object of study, it was used as a data collection technique for the survey of semi-structured questions. The results point out that the executives of the company can become aware of the need to be informed about the need of a business management system.